The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-35549-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen acquisition and resource allocation strategies in temperate seagrass Zostera nigricaulis: Uptake, assimilation and translocation processes

Abstract: The dominant seagrass in Port Phillip Bay (PPB), Australia, Zostera nigricaulis, declined between 2000 and 2011, coinciding with the ‘Millennium drought’ that ended in 2009. These seagrasses are nitrogen-limited, underpinning the need to develop nitrogen budgets for better ecosystem management. Environmentally realistic measurements of specific uptake rates and resource allocation were undertaken to develop nitrogen budgets and test the hypothesis that the above-ground and below-ground compartments are able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…2) which correspond to the oligotrophic environmental limit, and were found to be similar to the control experimental of local tap water at the root with NO 3 . This maximum cumulative response coincides with N de cit in aquatic plants roots [33] to the extent of limiting the growth of aquatic grasses by N in the oligotrophic environment, supporting the need to develop an endogenous pool of N [29]. Under oligotrophy conditions, the mean of NO 3 accumulation registered in local Vallisneria seedling was approximate to those reported on submerged species (root plus leaf), such as Berula erecta,…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…2) which correspond to the oligotrophic environmental limit, and were found to be similar to the control experimental of local tap water at the root with NO 3 . This maximum cumulative response coincides with N de cit in aquatic plants roots [33] to the extent of limiting the growth of aquatic grasses by N in the oligotrophic environment, supporting the need to develop an endogenous pool of N [29]. Under oligotrophy conditions, the mean of NO 3 accumulation registered in local Vallisneria seedling was approximate to those reported on submerged species (root plus leaf), such as Berula erecta,…”
Section: Resultssupporting
confidence: 63%
“…2). The order of descent of this ion was irregular with respect to NO 3 ion.DiscussionSubmerged grasses have been found sensitive to inorganic N excesses into the water column in shorttime, under both natural and semi-controlled environmental conditions[4,14,28,29]. In this contribution, a controlled environment (i.e.…”
mentioning
confidence: 92%
“…The preferential uptake of ammonium by seagrasses may be due to the physiological demands associated with nitrate uptake (Nayar et al, 2018 and references therein). Furthermore, seagrass tissues require far less energy than nitrate to transform ammonium into organic nitrogen (Nayar et al, 2018). Sandoval-Gil et al (2015) found that seagrass roots showed reduced capacity to absorb ammonium compared to leaves because of the very high availability of this nutrient in sediments.…”
Section: Discussionmentioning
confidence: 99%
“…While manatees may be eating C. caribensis because local food resources might be diminished, possibly due to global warming (e.g., O'Shea, 1986), some scientists propose that manatees eat invertebrates for the nitrogen within. Manatees living in marine habitats eat mostly seagrasses, which take-up nitrogen mostly through their leaves and are thought to be nitrogen limited (Duarte, 1990;Nayer et al, 2018). Up to 50% of nitrogen requirements of seagrasses are supplied by epiphytes living on the leaves, and seagrasses provide 8-22% protein per dry weight equivalent to corn and wheat (Walsh & Grow, 1972).…”
Section: Discussionmentioning
confidence: 99%